Implikasi Keterkaitan Model Pembelajaran Teacher Curatorial Studies Program Terintegrasi Residensi Galeri dalam Peningkatan Kompetensi Kuratorial Guru Seni Budaya - Iriaji; Yuliati; Usep Kustiawan; Ahmad Sholikin; Ageng Wiro Leksono; agengwiro103@gmail.com (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the implications of the relationship between the Teacher Curatorial Studies Program (TCSP) learning model that is integrated with gallery residency in improving the curatorial competence of cultural arts teachers. The TCSP model is designed to provide practical experiences through collaboration with art galleries that allow teachers to be directly involved in the curatorial process, including exhibition management and the drafting of artistic concepts. This study uses a qualitative approach with in-depth interview data collection techniques and observations of cultural arts teachers who participate in this program. The results show that the integration of gallery residencies enriches teachers' learning experiences in terms of organizing exhibitions, managing artworks, and effective visual communication. With hands-on mentoring and hands-on experience in the gallery, teachers' curatorial competence has significantly improved, which is reflected in their ability to design and present art exhibitions in schools. In addition, this model also contributes to increasing teachers' understanding of the importance of managing artworks that are contextual and relevant to local cultural dynamics. Overall, TCSP integrated gallery residencies proved effective in strengthening the curatorial skills of cultural arts teachers, which in turn had a positive effect on the quality of art teaching in schools.